Armenian Terrorism:: A Reappraisal - Gunter, Michael (Journal of Conflict Studies)

(untitled) (The University of New Brunswick, 2007)
Abstract This article reappraises the strategic impact of Armenian terrorism in the twentieth century. From 1973 to 1985, Armenian terrorists earned a deadly and infamous international reputation by murdering Turkish diplomats or members of their families, along with many other non-involved third parties killed in the crossfire, during 188 terrorist operations worldwide. By the mid-1980s, however, Armenian terrorists had fallen into mindless but deadly internal fighting that resulted in the deaths of several of their leading members. Yet even with the benefit of 20 years of hindsight, it remains difficult to assess definitively the strategic influence exerted by Armenian terrorism. It was an excellent example of how one person’s terrorist can be viewed by some as another’s freedom fighter. In seeking revenge for past perceived wrongs and in pursuit of the goal of an independent state, Armenian terrorism also shared common characteristics with such other ethnic-based terrorist movements as the Irish and Palestinians. Although by practically all conventional standards of measurement its ultimate strategic impact was virtually nil, some might still argue that Armenian terrorism did help preserve the memory of what many call the twentieth-century’s first or forgotten genocide.